From New Public Management to Public Sector Management Reforms during the pandemic. The effects of Covid-19 on public management reforms and effectiveness - Xanthopoulou, Panagiota; Plimakis, Iosif (Technium Social Sciences Journal, 2021)
The current paper presents some aspects and criticisms from the theoretical literature concerning the New Public Management (NPM). The article also critically examines whether the NPM model is appropriate and the drivers that affected its efficiency and effectiveness in the public sector especially in Greece, during the current pandemic. The research concluded that the process of managerial reform and the specific criteria in order to evaluate NPM’s effectiveness are not completed yet and that there are some key barriers such as the statist perception of citizens and politicians, the corruption of public, the fragmented organizational structures, the resistance to change that hinder the success of change and of NPM’s effective implementation in public sector. However, Covid-19 was a situation that helped many aspects of NPM such as digitalization, digital transformation, e-governance etc. to effectively be introduced and implemented in public governance of Greek organisations.